The Effects of High-fat-diet Combined with Chronic Unpredictable Mild Stress on Depression-like Behavior and Leptin/LepRb in Male Rats - Yang, Jin Ling (Sci Rep, 2016)
Leptin plays a key role in the pathogenesis of obesity and depression via the long form of leptin receptor (LepRb). An animal model of comorbid obesity and depression induced by high-fat diet (HFD) combined with chronic unpredictable mild stress (CUMS) was developed to study the relationship between depression/anxiety-like behavior, levels of plasma leptin and LepRb in the brains between four groups of rats, the combined obesity and CUMS (Co) group, the obese (Ob) group, the CUMS group and controls. Our results revealed that the Co group exhibited most severe depression-like behavior in the open field test (OFT), anxiety-like behavior in elevated plus maze test (EMT) and cognitive impairment in the Morris water maze (MWM). The Ob group had the highest weight and plasma leptin levels while the Co group had the lowest levels of protein of LepRb in the hypothalamus and hippocampus. Furthermore, depressive and anxiety-like behaviors as well as cognitive impairment were positively correlated with levels of LepRb protein and mRNA in the hippocampus and hypothalamus. The down-regulation of leptin/LepRb signaling might be associated with depressive-like behavior and cognitive impairment in obese rats facing chronic mild stress.